How Should Movement-Based Therapists Promote Physical Activity? A Delphi Study (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: The aim of the study is to develop a consensus among international experts on how movement-based therapists should promote physical activity. The action-based statements provide guidance on key methods, content, and principles to support movement-based therapists to increase physical activity in their patients in the long-term.Methods: We are conducting a Delphi study according to Hasson et al. (2000). An international Steering Group is responsible for study design, sample selection, as well as data collection and analysis. International experts in the field of physical activity promotion in healthcare have been recruited through purposive sampling. In the first Delphi round, qualitative data on suitable methods, content, and principles of physical activity promotion were collected to formulate initial statements. The data has been analysed using inductive category formation. In three further rounds, the statements will be refined, assessed in terms of their importance, and finally adopted by consensus. The threshold for consensus is at least 80% of agreement.Results: Results are currently available for the first Delphi round. Sixteen experts from ten countries participated. A total of 493 individual items were consolidated into 84 statements, which were categorised into 26 overarching themes. The derived statements relate to fundamental principles and concrete actions. Central themes include a person-centred approach and a focus on empowering patients.Conclusion: The study develops action-oriented statements based on expert consensus to promote physical activity in movement-based therapies. The results of the first round provide comprehensive insights into current approaches for promoting physical activity, which will be specified and prioritised in further Delphi rounds.Support/Funding Source: No funding was provided.